2019
DOI: 10.1136/bmjopen-2018-028131
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overweight and obesity and associated risk factors among adult residents of northwest China: a cross-sectional study

Abstract: ObjectiveOverweight and obesity have been shown to be related to multiple chronic conditions, leading to a heavy economic burden on society throughout the world. This study aims to estimate the prevalence of overweight and obesity and determine potential influencing factors among adults in Xinjiang, northwest China.DesignA community-based observational study.SettingThe First Affiliated Hospital of Xinjiang Medical University.MethodsIn total, 14 618 adult participants (7799 males; 6819 females) aged over 35 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 42 publications
14
33
0
Order By: Relevance
“…Obesity is caused by a complex interaction between the environment, genetic predisposition, and human behaviour. The high prevalence of overweight/obesity (nearly 40%) among respondents is consistent with findings of other studies which suggest rates of 30-50% [6,10,12]. The study found that being middle-aged; living in an urban community; not having regular physical activity and being a female were significant risk factors for overweight/obesity.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Obesity is caused by a complex interaction between the environment, genetic predisposition, and human behaviour. The high prevalence of overweight/obesity (nearly 40%) among respondents is consistent with findings of other studies which suggest rates of 30-50% [6,10,12]. The study found that being middle-aged; living in an urban community; not having regular physical activity and being a female were significant risk factors for overweight/obesity.…”
Section: Resultssupporting
confidence: 90%
“…There is no active and sustainable implementation of concise national policies on exercise and health promotion strategies targeting overweight/obesity as issues of public health concern. The association of female sex with overweight or obesity is in tandem with findings of other studies conducted globally [6,21,22]. Hormone-driven deposition of fat in the buttocks, hips, breast and abdomen occurs throughout the reproductive ages and predisposes women to overweight/obesity.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations